2013
DOI: 10.1111/mpp.12085
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tomato salicylic acid (SA)‐responsive pathogenesis‐related genes in Mi‐1‐mediated and SA‐induced resistance to root‐knot nematodes

Abstract: The expression pattern of pathogenesis-related genes PR-1, PR-2 and PR-5, considered as markers for salicylic acid (SA)-dependent systemic acquired resistance (SAR), was examined in the roots and shoots of tomato plants pre-treated with SA and subsequently infected with root-knot nematodes (RKNs) (Meloidogyne incognita). PR-1 was up-regulated in both roots and shoots of SA-treated plants, whereas the expression of PR-5 was enhanced only in roots. The over-expression of PR-1 in the whole plant occurred as soon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 43 publications
3
102
0
2
Order By: Relevance
“…PR proteins were initially reported in tobacco leaves during a hypersensitive response to the tobacco mosaic virus (TMV) [107,108] and have been induced in response a wide variety of pathogens including nematodes. During nematode infections, PR transcripts may accumulate in high concentrations and are associated with the long distance immune response termed systemic acquired resistance (SAR) [109]. Increased expression of PR-1(P4) transcripts was observed at 3 days' post-infection in the G. rostochiensis-infected resistant plants compared with the uninoculated controls [110].…”
Section: Pathogenesis-related Proteinsmentioning
confidence: 89%
See 1 more Smart Citation
“…PR proteins were initially reported in tobacco leaves during a hypersensitive response to the tobacco mosaic virus (TMV) [107,108] and have been induced in response a wide variety of pathogens including nematodes. During nematode infections, PR transcripts may accumulate in high concentrations and are associated with the long distance immune response termed systemic acquired resistance (SAR) [109]. Increased expression of PR-1(P4) transcripts was observed at 3 days' post-infection in the G. rostochiensis-infected resistant plants compared with the uninoculated controls [110].…”
Section: Pathogenesis-related Proteinsmentioning
confidence: 89%
“…The role of salicylic acid has been well documented in the eicacy of host resistance to root-knot nematodes. Pathogenesis-related protein expression was associated with salicylic acid-dependent systemic required resistance in tomatoes pretreated with salicylic acid under root-knot nematode challenge [109]. Expression of a NahG which encodes for an enzyme that degrades salicylic acid to catechol, reduced Mi-1 gene-mediated root-knot nematode resistance in transgenic tomatoes [135].…”
Section: Plant Hormonesmentioning
confidence: 99%
“…SAR is associated with increasing SA level by generating reactive oxygen species (ROS), enhancing activities of superoxide dismutase (SOD) and guaiacol peroxidase (GPOX), phytoalexin biosynthesis, accumulation of pathogenesis-related (PR) proteins (Pieterse and Van Loon 2007;Sahebani and Hadavi 2009;Molinari et al 2014). Recent study reported that chemical and microbial elicitors such as -aminobutyric acid (BABA), Salicylic acid (SA), and Pseudomonas fluorecens CHAO significantly reduced the RKN infection in tomato seedlings (Sahebani andHadavi 2009).…”
Section: Systemic Acquired Resistance (Sar)mentioning
confidence: 99%
“…Herman et al (2007) found that acibenzolar-S-methyl (ASM)-induced larger number of defense genes during second application compared to first application, indicating earlier induction of resistance genes does not negotiate the capability of the plant to react on later inductions. Meloidogyne incognita infection was demonstrated to elicit SAR in shoots of resistant plants carrying Mi-1 gene in where SA exogenously added as a soil drench (Molinari et al 2014). Interestingly, SA also has down regulatory role in effecting nematode-resistance gene Mi-1 so far have NBS-LRR domains (Sobczak et al 2005;Li et al 2006).…”
Section: Systemic Acquired Resistance (Sar)mentioning
confidence: 99%
“…[25] PR5 proteins are considered as markers for SAdependent SAR. [2,26] Like defensin gene, PR5 mostly changed significantly its expression (e.g. PR5 was up-regulated up to 235-fold in non-symptomatic plants of MS-2039A infected with broomrape from Soroca).…”
Section: Resultsmentioning
confidence: 99%